The interstellar medium in Andromeda's dwarf spheroidal galaxies: II. Multiphase gas content and ISM conditions - Looze, Ilse de; Cormier, Diane (Monthly notices of the Royal Astronomical Society, 2017)
We make an inventory of the interstellar medium material in three low-metallicity dwarf spheroidal galaxies of the Local Group (NGC 147, NGC 185 and NGC 205). Ancillary H i, CO, Spitzer Infrared Spectrograph spectra, Hα and X-ray observations are combined to trace the atomic, cold and warm molecular, ionized and hot gas phases. We present new Nobeyama CO(1-0) observations and Herschel SPIRE FTS [C i] observations of NGC 205 to revise its molecular gas content. We derive total gas masses of Mg = 1.9-5.5 × 105 M⊙ for NGC 185 and Mg = 8.6-25.0 × 105 M⊙ for NGC 205. Non-detections combine to an upper limit on the gas mass of Mg ≤ 0.3-2.2 × 105 M⊙ for NGC 147. The observed gas reservoirs are significantly lower compared to the expected gas masses based on a simple closed-box model that accounts for the gas mass returned by planetary nebulae and supernovae. The gas-to-dust mass ratios GDR ∼ 37-107 and 48-139 are also considerably lower compared to the expected GDR ∼ 370 and 520 for the low metal abundances in NGC 185 (0.36 Z⊙) and NGC 205 (0.25 Z⊙), respectively. To simultaneously account for the gas deficiency and low gas-to-dust ratios, we require an efficient removal of a large gas fraction and a longer dust survival time (∼1.6 Gyr). We believe that efficient galactic winds (combined with heating of gas to sufficiently high temperatures in order for it to escape from the galaxy) and/or environmental interactions with neighbouring galaxies are responsible for the gas removal from NGC 147, NGC 185 and NGC 205.